1986
DOI: 10.1159/000124568
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Endocrinological Aspects of Aging in the Rat Pineal Gland

Abstract: Previous morphological and biochemical studies point to an age-dependent loss of pineal gland function. In order to investigate the possible alterations of electrical activity of aged rat pineal glands, electrophysiological recordings in 3- and 18-month-old male Sprague-Dawley rats were undertaken at both daytime and nighttime. Extracellularly recorded action potentials were characterized according to discharge frequency and serum melatonin levels were determined concomitantly. Significant differences in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 32 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…Nocturnal plasma melatonin levels were decreased in both male and female 20‐month‐old control rats, relative to young rats. This is consistent with previous reports that nocturnal pineal melatonin content, as well as melatonin concentrations in circulation, decrease with aging in the rat [22–25, 32].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Nocturnal plasma melatonin levels were decreased in both male and female 20‐month‐old control rats, relative to young rats. This is consistent with previous reports that nocturnal pineal melatonin content, as well as melatonin concentrations in circulation, decrease with aging in the rat [22–25, 32].…”
Section: Discussionsupporting
confidence: 93%
“…Both the pineal melatonin secretory system [1, 2] and the forebrain POMC neuronal system [18–20] exhibit a circadian pattern of rhythmic activity, and constant light suppresses not only the circadian nocturnal secretion of melatonin [21] but also circadian changes in the forebrain POMC system [19]. Furthermore, aging‐related attenuation of the circadian amplitude of nocturnal melatonin secretion [4, 5, 22–25] appears to be temporally associated with a corresponding aging‐related decrease in forebrain POMC gene expression [26–28]. These associations, together with evidence that some central nervous system effects of melatonin are mediated by opioid mechanisms [21, 29], support the hypothesis that the pineal melatonin secretory system and the hypothalamic opiomelanocortinergic system, or mechanisms regulating these systems, may be functionally related.…”
Section: Discussionmentioning
confidence: 99%
“…A disappearance of day-night rhythm of melatonin in old and Alzheimer patients has been reported by Skene et al (1990). A decrease of pineal activity (Reuss et al, 1986), I accepted October 18, 1994 has been reported in old male rats (Reuss, 1980). We recently related the increase in the calcium content of pineal glands of aging rats (Humbert and PCvet, 1991) and the appearance of calcium concretions which have been reported earlier by Quay (1974).…”
Section: Introductionmentioning
confidence: 70%
“…This phenomenon may be linked to the decrease in electrical activity in old rats (Reuss et al, 1986), to the reduction of sympathetic innervation in aging animals, and the decline of the density of b-adrenergic receptors on pinealocytes membranes (Greenberg and Weiss, 1978;Henden et al, 1992), leading to a reduction of the metabolic activity of the gland.…”
Section: Cytoplasm Lp Cytoplasm Dp Mitochondria Dpmentioning
confidence: 99%
“…Previous reports indicate that nocturnal pineal melatonin content, as well as melatonin concentrations in circulation, decrease with aging in the rat [Reiter et al, 1981;Reuss et al, 1986;Pang et al, 1990;Bondarenko, 1992;Selmaoui and Touitou, 1999]. Pineal melatonin content in the middle-aged (12-month-old) female rat is intermediate between that of young adult and old rats [Reiter et al, 1981].…”
Section: Discussionmentioning
confidence: 96%